The Contemporary Classroom - Lange, Catilcia Prass (BELT - Brazilian English Language Teaching Journal, 2011)
This text makes a connection between a VEJA magazine’s article about present classroom and the discussion presented in RAMPTON, 2009 about a historical change in classroom participation. With that, this text invites teachers to reflect upon their own working reality in the schools and to operate in this new communicative order.